2001
DOI: 10.1053/eupc.2001.0188
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term atrial sensing stability in single-lead VDD pacing depends on right atrial dimensions

Abstract: According to our data, in VDD single-lead systems the amplitude of the atrial signal is stable over time in every physical activity. High RAD and low RAVD values may select patients with poor atrial sensing stability. Anyway, taking into account that no atrial oversensing was observed, atrial sensitivity setting at the highest value should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Enlargement of the atria was identified as a factor of higher prevalence of AF and lower likelihood of sinus rhythm restoration and maintenance [24,25]. Former studies have shown that the size of atria is correlated with mean AS amplitude and AS stability in VDD pacemakers [26,27]. This finding is consistent with our observations in this ICD population.…”
Section: Discussionsupporting
confidence: 83%
“…Enlargement of the atria was identified as a factor of higher prevalence of AF and lower likelihood of sinus rhythm restoration and maintenance [24,25]. Former studies have shown that the size of atria is correlated with mean AS amplitude and AS stability in VDD pacemakers [26,27]. This finding is consistent with our observations in this ICD population.…”
Section: Discussionsupporting
confidence: 83%
“…[17] The prevalence of atrial undersensing varied among different studies. [8] Santini et al [4] reported stable atrial signals over time in every physical activity, while extensive variation of atrial signal amplitude between postures was reported in another study. [18] Marchandise et al [19] found that up to one-third of VDD pacemaker patients could not maintain good atrial sensing after a mean follow-up of 2 years, which could mostly be ameliorated by increasing the atrial sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] However, available data about whether VDD is a good alternative to DDD are inconsistent. [6,7] Several trials have shown a comparable efficacy of VDD and DDD pacing, but with a lower cost for VDD, [6,810] while others demonstrated that up to one-third of patients with VDD failed to maintain AV synchronous pacing after years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the case of an EGM being of relatively low amplitude, most VDD pacemakers allow programming of a high sensitivity (0.1 mV for all models of our study, except for Medtronic Thera which was 0.18 mV) which may prevent atrial undersensing, without an undue risk of oversensing [7]. If intermittent atrial undersensing is present, it has been shown that if this occurs in < 10% of beats, exercise test results or quality-of-life are not affected [8].…”
Section: Discussionmentioning
confidence: 98%